Does Talking Stick Learning Model Improve Learning Outcome in Economics? - Saputra, Nadia Ulfa; Hardinto, Prih (Unversitas Negeri Malang, 2018)
Problems on the research of this learning are the application of the talking stick of the learning outcomes of students of Class XI IPS 1 in SMA Negeri 2 Pamekasan. The population in this research is the grade XI IPS 1 in SMA Negeri 2 Pamekasan with totaling 22 students. Consisting of 15 male students and 7 female students. Data retrieval method using interviews, tests, observations, field notes, and documentation. The research approach used in this study is a qualitative approach, whereas this type of research is action research class. The results of the research cycles I and cycles II suggests that indicators of success have been achieved, which includes an increase in student learning activities. In addition, the learning outcomes students also experienced an increase from cycle I to cycle II from 72.3% to 90.1%, with the achievement of the second cycle.